Sistem Otomatisasi Untuk Mengukur Kelembaban Suhu Dan pH Tanah Berbasis Android Menggunakan Arduino ESP32 Pada Tanaman Bayam (Studi Kasus : Syahmi Organik) - Dewa Fortuna; Hadi Zakaria (CV. Multi Kreasi Media, 2022)
Syahmi Organic is a home-based business that is engaged in food ingredients, especially vegetables, starting from land processing, planting, maintenance, and distribution of their products. The problems that are often experienced are the lack of human resources to analyze or regulate plantations on a regular basis and the lack of attention in monitoring the humidity, temperature and pH of the soil because no one always monitors the development of these plants which are needed in vegetable crops, especially spinach so that these plants cannot grow, well developed. To overcome this, the authors conducted a study by designing a system to monitor the humidity, temperature and pH of android-based soil using Arduino ESP32 on spinach plants. In making the system requires a device in the form of a microcontroller using several sensors such as a pH meter sensor, temperature sensor, humidity sensor and wifi module. In this study, the author uses the C programming language, and the database used is firebase and the waterfall model as the design flow. With a monitoring system using this microcontroller, it is hoped that it can help farmers to get maximum and quality harvests. To be able to access this microcontroller tool, farmers can use an Android-based application that is already connected to the tool, and farmers can measure the moisture and soil pH of the plant directly through an Android application that is connected to the internet.